Digital fundamentals - Floyd, Thomas L. (Prentice Hall, 2003)
Offers coverage of digital fundamentals--from basic concepts to microprocessors. Floyd's emphasis on applications using real devices and on troubleshooting gives students the problem-solving experience they'll need to compete in the professional arena.